2011
DOI: 10.30638/eemj.2011.032
|View full text |Cite
|
Sign up to set email alerts
|

Aspects Regarding Recycling Sludge by Composting\

Abstract: It has been an increased interest in using sewage sludge as agricultural fertilizer and soil improvement material, especially as compost with biomass. This paper analyses five samples of composts from bio waste and sewage sludge, with various percentage of sludge, using the following parameters: pH, EC, carbohydrates content, enzymes content and C: N ratio. The results were correlated with FT-IR spectra and germination test in order to assess the stability and maturity of the composts samples. It was also calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
3
1
Order By: Relevance
“…A similar decrease in pH over the maturation was reported by Troy et al [40]. All the EC values in this study fell below the recommended limit provided by [41], and even below what was reported by [39], and are therefore considered safe for agricultural applications. The high EC values obtained from bfr6 and bfr5 are a reflection of nutrient enrichment [41].…”
Section: The Chemical Characteristics Of Horse Waste-based Bokashi Fe...supporting
confidence: 87%
See 1 more Smart Citation
“…A similar decrease in pH over the maturation was reported by Troy et al [40]. All the EC values in this study fell below the recommended limit provided by [41], and even below what was reported by [39], and are therefore considered safe for agricultural applications. The high EC values obtained from bfr6 and bfr5 are a reflection of nutrient enrichment [41].…”
Section: The Chemical Characteristics Of Horse Waste-based Bokashi Fe...supporting
confidence: 87%
“…All the EC values in this study fell below the recommended limit provided by [41], and even below what was reported by [39], and are therefore considered safe for agricultural applications. The high EC values obtained from bfr6 and bfr5 are a reflection of nutrient enrichment [41]. The EC value in bfr6 was 459% higher than what was obtained in the control (bfr1).…”
Section: The Chemical Characteristics Of Horse Waste-based Bokashi Fe...contrasting
confidence: 46%
“…At the end of composting, as result of aerobic oxidative biodegradation of organic matter by composting, a reduction of numbers of bands characteristic to the aliphatic polymeric compounds (poly carbohydrates, proteins, lipids) and an increasing of absorption bands (700-1,000 cm −1 ) characteristic to the aliphatic and oxidized aromatic organic compounds such as carboxylic acids (-COO-ions in organic acids and their salts), carbonyl compounds (aldehydes, ketones, quinones), aromatic compounds formed by lignin biodegradation (phenols, amides, aromatic aldehydes, monosubstituted arenes were observed [12,56,60]). …”
Section: Ft-ir Analysismentioning
confidence: 99%
“…and decarboxilation products of proteins and lipids [3,15]. Further increasing of pH (weeks 4-9) may be caused by decomposition of organic matter containing nitrogen (proteins, amino acids) and mineralization of organic nitrogen through microbial activities leading to formation of ammonia [56]. The pH values at the end of composting period (9 weeks) are between 7.28 and 9.00, decreasing after the maturation period at 6.68-6.96, a pH value considerate optimum for using as bio fertilizers (see Fig.…”
Section: Monitoring the Composting Processmentioning
confidence: 99%
See 1 more Smart Citation